The Influence of Motorcycle Educability on the Ability of Basic Sickle Kick Techniques in Pencak Silat Extracurricular Students at SMPN 1 Majalaya - Ginanjar Bagus Sajiwo; Sapeul Ma'mun; Aria Kusuma Yuda (Universitas Riau, 2024)
Extracurricular activities are educational activities outside of school subjects to help develop students according to their needs, potential, talents and interests through activities specifically organized by educators and authorized teaching staff at school. The aim of this research was to find out the influence of motorbike educability on the ability of basic crescent kick techniques in pencak silat extracurricular students at SMPN 1 Majalaya. The method used in this writing is an experiment with a One-Group Pretest-Posttest design. The data analysis technique uses tests. The prerequisites for analysis are the normality test using the Shapiro-Wilk test, simple linear regression test and t test. The sample in this study was 20 students of SMPN 1 Majalaya who were taken using total sampling technique. Based on the research results, it can be concluded that there is a comparison between t count and t table of t count 6.537 > t table 1.729, meaning that Ho is rejected and Ha is accepted or it can be said that motor educability (X) really has a significant influence on basic technical abilities crescent kicks for pencak silat extracurricular students at SMPN 1 Majalaya.